REALISME KRITIS: PEMAHAMAN BARU TENTANG PENELITIAN ILMU SOSIAL - Wuisman, Jan (P2KK LIPI, 2004)
Critical realism is a current in philosophy of social science, which emerged in the 1970s in the United Kingdom as a reaction toward two other currents in philosophy of science that in the past dominated the natural sciences: positivism and idealism. In the 1980s the scope of critical realism was extended to include the social sciences. Critical realism claims to present a new view and better understanding of the practice of social research compared to those currently in sway. The philosophy of science presented by critical realism is quite complicated, but important enough to be given serious attention. The purpose of this article is to discuss a number of topics which crucial for the proper understanding of the current of philosophy of science as well as its implications for the practice of research in the social science.